The concept of asceticism and its virtues and his difference from mysticism and monasticism (Journal of the College of Basic Education, 2022)
The subject of asceticism is one of the most important religious and ethical issues; Away from all the impurities and false meanings and false, which the people of innovation, such as false mysticism, isolation, monasticism and many other meanings and things that are considered extraneous to the Islamic religion.in this research to the definition of asceticism language and terminology, as well as the description of asceticism, and the credit that occurs to the slave of asceticism in the world, and showed the difference between asceticism and other concepts such as mysticism and monasticism, as the asceticism does not prevent life, but on the contrary call for a dignified and happy life for individuals،And concluded that the meaning of asceticism is the lack of value of the thing, Aststgharh, and against the desire in it, and not to pay attention to it, it is asceticism in the world, did not make his concern to them, that asceticism is not meant to live in isolation from the world and society, and isolation, but be asceticism in dealings All of them, and followed the research methodology objective